2011
DOI: 10.1183/09031936.00001711
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide association study reveals evidence of association with sarcoidosis at6p12.1

Abstract: Sarcoidosis is a complex systemic inflammatory disease of unknown aetiology that is influenced by a variety of genetic and environmental factors.\ud To identify further susceptibility loci for sarcoidosis, a genome-wide association study (GWAS) was conducted in 381 patients and 392 control individuals based on Affymetrix 100k GeneChip data. The top 25 single-nucleotide polymorphisms (SNPs) were selected for validation in an independent study panel (1,582 patients versus 1,783 controls).\ud Variant rs10484410 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 34 publications
1
25
0
1
Order By: Relevance
“…Thus, in susceptible individuals, inanimate remnants of bacteria or remote infection may be capable of inducing sustained sarcoid-like inflammation (51,52). The nature of these disease susceptibilities may be queried in genome-wide association studies, which have identified a number of gene variants associated with sarcoidosis and other granulomatous disorders (53)(54)(55). Another approach is the identification of molecular signatures by systems biology approaches using peripheral blood cells or lung tissue.…”
Section: Other Dplds Sarcoidosismentioning
confidence: 99%
“…Thus, in susceptible individuals, inanimate remnants of bacteria or remote infection may be capable of inducing sustained sarcoid-like inflammation (51,52). The nature of these disease susceptibilities may be queried in genome-wide association studies, which have identified a number of gene variants associated with sarcoidosis and other granulomatous disorders (53)(54)(55). Another approach is the identification of molecular signatures by systems biology approaches using peripheral blood cells or lung tissue.…”
Section: Other Dplds Sarcoidosismentioning
confidence: 99%
“…Autoantigens may derive from misfolded proteins that are insufficiently cleared. It could be demonstrated that single-nucleotide polymorphisms in the OS9 [21] and RAB23 [22] genes are associated with an increased risk of sarcoidosis. Both genes are assumed to be involved in the regulation of the degradation of misfolded proteins or the generation of autophagosomes.…”
mentioning
confidence: 99%
“…Familial clustering of sarcoidosis may be found in 5-10% of patients, and represents, together with genome-wide scanning for susceptibility genes [28], one of the best ways to progress in the understanding of this disease of elusive aetiology. In 2005, dentification of butyrophilin-like-2 as a main genetic determinant of sarcoidosis was reported [29].…”
mentioning
confidence: 99%